Peningkatan Pengetahuan Remaja Terhadap Dampak Cemaran Kimia pada Jajanan - Prastiwi, Ratih Sakti; Maulida, Iroma; Arisanti, Novia Ludha (Jurnal Pengabdian Dharma Bakti, 2019)
Most of snacks or foods at school contained many dangerous chemical material which is dangering students health. When students consumed it in long periode resulting indigestion, respiratory disorder, neurological disorder, liver damage, cancer and reproductive health. This activitiy was being held to increase students knowledge to change their attitude and behavior in choosing foods and snacks. By this activity, it was found that most students lack of knowledge about chemical contamination damage for their health. Therefore, by sharing health information, students could understands that consuming foods contained chemical material in long periode causing various health problems including reproductive health. After they received those informations, students had better understanding about chemical contamination damage but also how to identify which foods are contaminated. The post tets scores have increase by 25%. So it could be conclude that, by sharing health information, students had better understanding and formed attitude to do positive thing.Keywords: knowledge, chemical contamination, teenager, foods